Desain Tangki Klakson pada Mobil untuk Penyimpanan Udara Bertekanan 8 bar - Samosir, Reynaldi; Jufrizal, Jufrizal; Arif, Zainal (IRA Jurnal Teknik Mesin dan Aplikasinya (IRAJTMA), 2025)
The air tank is a crucial component in pneumatic car horn systems, serving to store compressed air to produce a loud and responsive sound. Most pressure vessel studies have focused on high-pressure applications in industry. At the same time, research on low-pressure tanks for automotive use remains limited, particularly those referring to ASME Section VIII Division 1 standards. This study designed a horizontal cylindrical air tank using the thin-walled cylinder approach with steel plates (yield strength 250 MPa, safety factor 4). The analysis showed a minimum wall thickness of 1.18 mm, while the actual thickness of 3 mm provides additional safety margins. The circumferential stress of 24.67 MPa and longitudinal stress of 12.34 MPa are well below the allowable stress of 62.5 MPa. These results confirm that the design is safe and efficient, contributing to the development of low-pressure pressure vessels for automotive applications.